2017
DOI: 10.1158/1541-7786.mcr-16-0218
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA Integrity Is Maintained by APE1 in Carcinogen-Induced Colorectal Cancer

Abstract: Changes in mitochondrial DNA (mtDNA) integrity have been reported in many cancers, however, the contribution of mtDNA integrity to tumorigenesis is not well understood. We used a transgenic mouse model that is haploinsufficient for the apurinic/apyrimidinic endonuclease 1 (Apex1+/-) gene, which encodes the base excision repair (BER) enzyme APE1, to determine its role in protecting mtDNA from the effects of azoxymethane (AOM), a carcinogen used to induce colorectal cancer (CRC). Repair kinetics of AOM-induced m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 47 publications
(62 reference statements)
0
14
0
Order By: Relevance
“…Mitochondrial dysfunction is believed to play a role in Huntington's disease pathology, and prior studies have demonstrated that APE1 is important for the maintenance of mitochondrial function (Li et al ., 2012; Siddiqui et al ., 2012). APE1 is also known to participate in mitochondrial DNA repair functions (Ballista‐Hernandez et al ., 2017; Stuart et al ., 2004; Vascotto et al ., 2009). While APE1 is known to influence these pathways, this study expands our understanding of APE1 within the cell by implicating the genes in the pathways that are affected by APE1 knockdown.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mitochondrial dysfunction is believed to play a role in Huntington's disease pathology, and prior studies have demonstrated that APE1 is important for the maintenance of mitochondrial function (Li et al ., 2012; Siddiqui et al ., 2012). APE1 is also known to participate in mitochondrial DNA repair functions (Ballista‐Hernandez et al ., 2017; Stuart et al ., 2004; Vascotto et al ., 2009). While APE1 is known to influence these pathways, this study expands our understanding of APE1 within the cell by implicating the genes in the pathways that are affected by APE1 knockdown.…”
Section: Resultsmentioning
confidence: 99%
“…One previously linked pathway of particular interest is the mitochondrial dysfunction pathway. APE1 redox and repair activity has previously been shown to be responsible for maintaining and repairing mitochondrial DNA (Ballista‐Hernandez et al ., 2017; Li et al ., 2012; Siddiqui et al ., 2012; Stuart et al ., 2004; Vascotto et al ., 2009). The results of our studies presented here identify, for the first time, the genes responsible for these functions.…”
Section: Discussionmentioning
confidence: 99%
“…The primer sequences were as follows: Cox2, 5’-GCCGACTAAATCAAGCAACA-3’ (forward) and 5’-CAATGGGCATAAAGCTATGG-3’ (reverse); and β-globin, 5 ‘-GAAGCGATTCTAGGGAGCAG-3’ (forward) and 5’-GGAGCAGC GATTCTGAGTAGA-3’ (reverse). The relative mtDNA to nuclear DNA copy number ratio was determined using the comparative DDCT method (Ballista-Hemandez et al, 2017; Gonzalez-Hunt et al, 2016; Lien et al, 2017), in which NDl/β-globin and Cox2/β-globin ratios were calculated.…”
Section: Methodsmentioning
confidence: 99%
“…APE1/Ref-1 interacts with the mitochondrial import and assembly protein Mia40, which is responsible for APE1/Ref-1 trafficking into the mitochondria [42]. A recent study using haploinsufficient APE1/Ref-1 mice revealed slower repair kinetics of azoxymethane-induced mitochondrial DNA damage, suggesting that APE1/Ref-1 is important for preventing changes in mitochondrial DNA integrity during azoxymethane-induced colorectal cancer [43].…”
Section: Cytoplasmic Function Of Ape1/ref-1mentioning
confidence: 99%